PENGARUH FINE COMPOST DAN RAPTHANE TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH - Rijono Eko Muharijanto (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This research was conducted on the grounds that shallots have multiple uses and high economic value as well as good market opportunities, while Fine Compost and Repthane contain plant nutrients and soil microbial media as well as facilitate the metabolism of P element absorption. This study aims to determine the effect of using Fine Compost and Rapthane. on the growth and production of shallots. The research was carried out in Kemiri Village, Jenangan District, Ponorogo Regency with dark brown Mediterranean soil type with a height of 675 m above sea level. The study used a Randomized Block Design (RAK) method with 2 treatment factors consisting of 3 and 4 levels each with 3 replications, namely the treatment factor using Rapthane; P0; without Rapthane, P1; The use of Rapthane 3 cc/liter of water, P2; The use of Rapthane 4 cc/liter of water and treatment factors for the use of Fine Compost with code F0: without Fine Compost, F2: the use of Fine Compost 1 ton/ha, F2: the use of Fine Compost 2 tons/ha, F3: the use of Fine Compost 3 tons/ha . Observations were made on the sample clumps of each treatment plot of three clumps at random diagonally at the time of observation on plants aged 15, 30 and 45 DAP. Observation parameters consisted of the growth phase including plant height and number of leaves, while in the production phase the number of tubers and tuber weight. The results of the study were tested using analysis of variance and the smallest significant difference test (BNT) at the level of 0.05. From the results of the analysis of variance and the BNT test, it showed that the interaction of Rapthane and Fine Compost fertilizer in the study of the effect of PPC fertilizer and Fine Compost fertilizer did not show a significant effect except for the number of leaves at the age of 15 days after planting, this was because both Rapthane and Fine Compost were the same. containing the element N is very large role for vegetative growth on the number of leaves this is possible because of the influence of the availability of nutrients Nitrogen (N) due to Phosphorus (P) which is sufficient in addition to the guaranteed development of soil microbes. The effect of Rapthne 4 cc/l of water can increase the number of leaves and plant height at the age of 30 and 45 days after planting, as well as the number of tubers and tuber weight. The effect of Fine Compost 2 tons/ha significantly affected the number of leaves, plant height, number of tubers and tuber weight.